The Relationship Among OIL Prices, Gold Prices, Gross Domestic Product, and Interest Rate to the Stock Market Return of Basic Industry and Chemical Sector in Indonesia in 2005-2013 - Singarimbun, Ceria Minati; Noveria, Ana (Journal of Business and Management, 2014)
In this research author try to analyze the relationship among oil price, gold price, gross domestic product, and interest rate to the stock market return on basic industry and chemical sector in Indonesia in the period of 2005-2013. To seek the relationship among these variables, author conducts several methods, which are the classic assumption tests, multiple linear regression, and Hypothesis testing by using F test and T test. These methods will reveal the effect of each variable, as the factor of economic activity, towards the stock return of basic industry and chemical companies which listed in Jakarta Composite Index since 2005 to 2013.The result represented that some variables significantly influenced the stock return, one variable does not really significantly influenced the stock return, and one variable should be taken off because it could not pass the method. In the earlier of examining the classic assumption test, author brought 4 variables, which are Oil Price, Gold Price, GDP, and Interest Rate. During running the multicollinearity test, it was found that the GDP and Gold Price has a correlation so one of them should be take off, which is Gold Price. After completing the entire test, author found that Oil Price and Interest Rate significantly influence the value of stick return. Thus, if the oil price or interest rate in the actual financial market increases, the value of stock return will be decreased. Meanwhile, GDP has lower significance level to influence the value of stock return or in the other words; GDP does not significantly influence the value of stock return regarding its low value of multiplier. But the value of GDP will increase the value of stock return.Keywords: Multiple Linear Regressions, Oil Price, Gold Price, Interest Rate, GDP, Stock Return, Basic Industry and Chemical Companies, Jakarta Composite Index.